2005
DOI: 10.1152/ajpheart.00640.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a “falx lunatica” in demarcation of critically ischemic myocutaneous tissue

Abstract: Using intravital microscopy in a chronic in vivo mouse model, we studied the demarcation of myocutaneous flaps and evaluated microvascular determinants for tissue survival and necrosis. Chronic ischemia resulted in a transition zone, characterized by a red fringe and a distally adjacent white falx, which defined the demarcation by dividing the proximally normal from the distally necrotic tissue. Tissue survival in the red zone was determined by hyperemia, as indicated by recovery of the transiently reduced fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The absence of signs of angiogenesis, which should be visible after ∼day 3, might be due to desiccation of the tissue within the chamber. The transitory zone of demarcation between the perfused area of the flap proximally and the necrotic area distally adjacent revealed an increased microvascular stasis, arterio-venular dilation, and hence tortuosity but no signs of angiogenesis, representing a zone of compromised blood perfusion as previously shown [22].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The absence of signs of angiogenesis, which should be visible after ∼day 3, might be due to desiccation of the tissue within the chamber. The transitory zone of demarcation between the perfused area of the flap proximally and the necrotic area distally adjacent revealed an increased microvascular stasis, arterio-venular dilation, and hence tortuosity but no signs of angiogenesis, representing a zone of compromised blood perfusion as previously shown [22].…”
Section: Discussionsupporting
confidence: 71%
“…Accordingly, only after ET-B-receptor blockade capillary perfusion was found improved during the first days after flap elevation. In fact, the values of FCD after ET-B-receptor blockade were in the range of the physiologic values of intact tissue within dorsal skinfold chamber preparations [18,22]. Assessment of FCD after blockade of the ET-A receptor or both the ET-A and ET-B receptor revealed that the late recovery of aBF was not anymore capable of improving capillary perfusion.…”
Section: Discussionmentioning
confidence: 90%
“…The critically perfused zone of demarcation of a flap consists of an area with a rarefaction of perfused capillaries that dilate in order to increase the exchange surface of O 2 between vessels and interstitial tissue, i.e., to increase O 2 conductance [2]. These scarce microvessels may not serve as an adequate nutritional supply to the tissue but only function as "thoroughfare" channels, as described for .…”
Section: Discussionmentioning
confidence: 99%
“…Insufficiency of the microcirculation on the other hand may lead to irreversible tissue damage due to persistent ischemia and hypoxia, which untreated will result in wound breakdown [1] and compromised tissue survival, including surgical accesses with extensive undermining or randomly perfused remote areas of the critically perfused flap tissue [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the microcirculation and partial oxygen tension in different zones of the myocutaneous flap revealed that the critical ischaemia-induced necrosis does not demarcate sharply from the adequately perfused tissue at the flap basis (Harder et al, 2005a). Between the two zones a fringe of tissue with vascular remodelling develops a distally adjacent falx lunatica lacking nutritive www.ecmjournal.org…”
Section: Mw Laschke and MD Mengermentioning
confidence: 99%